Desain Pemodelan Andongan Dan Ketegangan Untuk Saluran Transmisi 275 KV Menggunakan Metode Catenary - Dicky Novriandi; Azriyenni Azhari Zakri; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research develops a method for determaining catenary sag and tension analysis on 275 kV transmission line conductors. Catenary method is a function of the weight equation conductor, wires maximum tensile stress, long-span, and the maximum sag of the conductor. Processing methods was is used to determaine the value of the sag and tension with the design of the model using statistical software AutoCAD, as well as determining the value of sag and tension of the influence of temperature conductor due to the current flow and ambient temperature using data conductor types A1/SA1A (ACSR/AS), the results of this research for the same tower height is obtained sag of 6.86 m, with a value of 4610.83 kg tension and conductor length of 401.06 m, while sag value for the tower which is placed at the high of 35.22 m, and sag for tower which is placed on the lower section of 0.48 m, the value of tension obtained for towers placed at a high part is 4657 kg while the tension value for towers placed in the lower part is 4600.75 kg, and the value change in conductor length by 401,882 m. Any increase in the current then sag value will increase, when the minimum current generated sag value of 6.8621 m, when the maximum current the resulting sag value increases to 8.31 m. While the value of tension obtained will be reduced, when the minimum current value of the tension is 4610,538 kg, when the maximum current value of tension is 3811,159 kg, Any increase in ambient temperature sag value will increase, when the minimum temperature is 20℃ the resulting sag value of 6.8621 m then when the maximum temperature is 40℃ the resulting sag value increased to 7.793492 m, While the value of the tension will decrease, when the minimum temperature value amounted tension 20℃ 4610.538 kg, when the maximum temperature is 40℃ tension value of 4062.345 kg.Keywords: ACSR, Catenary, Sag, Tension, Transmission Line.